Paediatric Respiratory Epidemiology 2021
DOI: 10.1183/13993003.congress-2021.oa2958
|View full text |Cite
|
Sign up to set email alerts
|

Increased impact of air pollution on lung function in preterm vs. term infants: the BILD study

Abstract: Air pollution and postnatal lung function in preterm infantsDescriptor number: 14.3 Total word count: text 3494/3500 Today, approximately 10% of all infants are born prematurely, pre-existing vulnerability means that their lungs are potentially more susceptible to ambient air pollution. This is the first study showing that the effect size of low-to-moderate levels of air pollution exposure during pregnancy on postnatal lung function is significantly higher in preterm than in healthy term infants of similar pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 0 publications
3
8
0
Order By: Relevance
“…While an isolated decrease in FEV 0.5 may be a sign of airway obstruction, the concomitant decrease in FVC could indicate a generally smaller lung volume. Both narrower airways and smaller lung volumes provide explanations for the increase in minute ventilation and respiratory need observed in our, as well as in earlier studies in infancy 8,9,15 . The mechanisms behind the inverse association between air pollution and infant lung function are likely to be multifactorial, but growth factors affecting lung size may be of interest 4,24 .…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…While an isolated decrease in FEV 0.5 may be a sign of airway obstruction, the concomitant decrease in FVC could indicate a generally smaller lung volume. Both narrower airways and smaller lung volumes provide explanations for the increase in minute ventilation and respiratory need observed in our, as well as in earlier studies in infancy 8,9,15 . The mechanisms behind the inverse association between air pollution and infant lung function are likely to be multifactorial, but growth factors affecting lung size may be of interest 4,24 .…”
Section: Discussionsupporting
confidence: 69%
“…Air pollution can contribute to airway disease and dominating parts of the population in urban areas across the world are exposed to levels exceeding the health based guidelines proposed by the World Health Organisation 5 . Several epidemiological studies have shown inverse associations between air pollution exposure and lung function in children 6‐15 . In particular, there is evidence that early life exposure affects lung function measured later in childhood, 6,11,12,14 as well as in adulthood 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early life is a critical period of airway and lung development and especially relevant in terms of long-term effects on respiratory health. D ecrue et al [ 60 ] observed among 254 preterm and 517 term infants of the Basel-Bern Infant Lung Development cohort [ 61 ] that higher particulate matter of less than 10 µm during the second trimester of pregnancy was associated with lower lung function and higher oxidative stress shortly after birth. Participants exposed to low-to-moderate air pollution levels and the effects observed were stronger among preterm infants [ 60 ].…”
Section: Group 76: Paediatric Respiratory Epidemiologymentioning
confidence: 99%
“…D ecrue et al [ 60 ] observed among 254 preterm and 517 term infants of the Basel-Bern Infant Lung Development cohort [ 61 ] that higher particulate matter of less than 10 µm during the second trimester of pregnancy was associated with lower lung function and higher oxidative stress shortly after birth. Participants exposed to low-to-moderate air pollution levels and the effects observed were stronger among preterm infants [ 60 ]. A bellan et al [ 62 ] applied unique exposome approaches among 5624 mother–child pairs from the Generation R birth cohort [ 62 ].…”
Section: Group 76: Paediatric Respiratory Epidemiologymentioning
confidence: 99%